2012
DOI: 10.1021/tx3003033
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiencies of Damage Recognition and Excision Correlate with Duplex Destabilization Induced by Acetylaminofluorene Adducts in Human Nucleotide Excision Repair

Abstract: Nucleotide excision repair (NER) removes lesions caused by environmental mutagens or UV light from DNA. A hallmark of NER is the extraordinarily wide substrate specificity, raising the question of how one set of proteins is able to recognize structurally diverse lesions. Two key features of good NER substrates are that they are bulky and thermodynamically destabilize DNA duplexes. To understand what the limiting step in damage recognition in NER is, we set out to test the hypothesis that there is a correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 46 publications
(146 reference statements)
3
36
1
1
Order By: Relevance
“…The lower band is attributed to a single XPC molecule-DNA complex and the higher one is attributed to complexes with two XPC molecules bound per DNA molecule. Similar double-molecule XPC-RAD23B -DNA complexes have been reported by other workers [10, 4042]. However, when an adduct is present, the two bands are no longer distinguishable.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The lower band is attributed to a single XPC molecule-DNA complex and the higher one is attributed to complexes with two XPC molecules bound per DNA molecule. Similar double-molecule XPC-RAD23B -DNA complexes have been reported by other workers [10, 4042]. However, when an adduct is present, the two bands are no longer distinguishable.…”
Section: Resultssupporting
confidence: 86%
“…The NER excision efficiencies of adducts have been found to be correlated with the binding affinities of XPC-RAD23B [10]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the lack of direct contact with the lesion by Rad4, Rad4 (XPC) is proposed to indirectly recognize locally destabilized duplex DNA by probing the two strands’ propensity to open, which allows insertion of β-hairpin 3 (Min and Pavletich, 2007). This hypothesis provides a working model for how Rad4 (XPC) recognizes chemically and structurally diverse DNA damage in vitro , such as a cholesterol-modified nucleotide, 6-4PP, cisplatin 1,3-d(GTG) intrastrand adduct, C8-dG acetylaminofluorene, and 5R-thymine glycol (Brown et al, 2010; Hey et al, 2002; Jansen et al, 1998; Kusumoto et al, 2001; Sugasawa et al, 2002; Yeo et al, 2012). Previous studies on domain deletions and mutated XPC constructs employing bulk biochemical binding assays and a fluorescence-based cellular method suggest a two-stage damage recognition model.…”
Section: Introductionmentioning
confidence: 99%
“…These properties were originally framed in the context of the bipartite recognition model that posits that good NER substrates are destabilizing and bulky (Hess et al 1997). Subsequent studies correlating the structures of adducts such as those formed by benzo[a]-pyrene or acetylaminofluorene with their repair efficiencies confirmed these observations and showed that factors such as disrupted base-pairing, bending, and flexibility can contribute to repair outcomes Cai et al 2010;Mu et al 2012;Yeo et al 2012). As discussed in the next section, we now understand these principles in terms of how damage recognition is achieved in NER.…”
Section: The Core Ner Reaction Different Modes Of Damage Recognition mentioning
confidence: 99%